Comment penser l’informalité dans les villes « du Nord », à partir des théories urbaines « du Sud » ? - Sébastien Jacquot; Marie Morelle (Métropoles)
Since the mid-2000’s, several Anglophone authors have reevaluated the role of cities from the Global South within urban studies and the production of urban theory, seeking to break with the previous normative approach. As a result of this changing epistemological perspective, a network has been created to destabilize Northern theory and to problematize urban theory from the South. The concept of urban informality has become a key notion in this reproblematization of urban studies from the South. Taking into account these epistemological dynamics, our aim is to investigate this north-south divide within urban and planning studies. To what extent can the notion of informality, which was developed to explain southern urban societies, also be useful to understand urban dynamics in the North? Building on a shift from economic informality to political informality, we study the reconfigurations of public policies in cities spanning the north-south divide. We focus on the plurality of public policies and the ways in which they tolerate, or in some cases regulate, informal economic activities. This research is based on a critical theoretical analysis as well as field observations of street vendors and migrants in Genova (Italy) and street car repair in Seine Saint Denis (Paris suburbs).